Model Promosi Kesehatan Sebagai Upaya Pencegahan Stunting Melalui Program Kesehatan Ibu dan Anak (KIA) - Osi Draini; Siti Zahara Nasution; Arlinda Sari Wahyuni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify an effective health promotion model in efforts to prevent stunting through the Maternal and Child Health program at the Tembilahan Health Center, Riau Province. This research is a quantitative research using Quasi Experiments with a pre and post-test control group design approach. The research sample was 102 women of childbearing age, namely 34 people in each group who were taken using the consecutive sampling technique. Data collection using a questionnaire. Univariate and bivariate data analysis using paired t-test statistics. The results showed that there were differences in the increase in knowledge in the treatment group p=0.000 (p<0.05) and there were differences in attitudes in the treatment group and the control group p=0.000 (p<0.05). In conclusion, a health promotion model that is effective in providing increased knowledge is a health promotion model of lectures and leaflet media and a health promotion model that is effective in providing attitude changes is a health promotion model of lectures and video media. Keywords: Health Promotion, Maternal and Child Health, Stunting.